2016
DOI: 10.1093/annonc/mdv541
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial of intensive versus minimal surveillance of patients with resected Dukes B2-C colorectal carcinoma

Abstract: NCT02409472.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
84
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(86 citation statements)
references
References 11 publications
1
84
0
1
Order By: Relevance
“…Similar conclusions were reached in the GILDA (Gruppo Italiano di Lavoro per la Diagnosi Anticipata) trial, an RCT comparing imaging follow‐up strategies for colorectal cancer, in which 1228 patients were randomized to either minimal or intensive surveillance. Liver ultrasonography was performed twice over the 5‐year study period in the minimal surveillance group, compared with every 4 months in the first year and often combined with chest X‐rays in the intensive surveillance group.…”
Section: Discussionsupporting
confidence: 66%
“…Similar conclusions were reached in the GILDA (Gruppo Italiano di Lavoro per la Diagnosi Anticipata) trial, an RCT comparing imaging follow‐up strategies for colorectal cancer, in which 1228 patients were randomized to either minimal or intensive surveillance. Liver ultrasonography was performed twice over the 5‐year study period in the minimal surveillance group, compared with every 4 months in the first year and often combined with chest X‐rays in the intensive surveillance group.…”
Section: Discussionsupporting
confidence: 66%
“…The Italian GILDA study 85 examined the addition of ultrasound to CEA-based follow-up of colorectal cancer patients, although, confusingly, rectal cancer patients were also permitted a CT scan. As ultrasound is an insensitive method of examining for recurrence, and as all patients had regular CEA measurement, it is unsurprising that the experimental arm in this study did not demonstrate benefit.…”
Section: Discussionmentioning
confidence: 99%
“…As ultrasound is an insensitive method of examining for recurrence, and as all patients had regular CEA measurement, it is unsurprising that the experimental arm in this study did not demonstrate benefit. 85 A French study registered on ClinicalTrials.gov (NCT00199654) examines the use of PET compared with conventional imaging and CEA testing. The end point is time to diagnosis of recurrence, and the study authors planned to recruit 376 patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, the authors found that methods were poorly reported and concluded that ‘large trials are required to identify which components of intensive follow up are most beneficial’. Since then, three large trials of intensified monitoring have reported. An updated search, systematic review and meta‐analysis have been undertaken to examine the effect of these programmes on overall survival including all randomized studies identified.…”
Section: Introductionmentioning
confidence: 99%